Perencanaan Tebal Perkerasan Kaku Ruas Jalan Raya Jepara Bangsri pada Km 11 sampai Km 12 Menggunakan Pedoman Bina Marga 2017 - Rochmanto, Decky; Adi Saputro, Yayan; Tiara, Mayang (Jurnal Civil Engineering Study, 2022)
The damage that occurs due to increased intensity of vehicle loads that come and transport goods on Jalan Raya Jepara - Bangsri so that the pavement layer received increases along with the increase in traffic volume on the road. For this reason, it is necessary to plan a new pavement using rigid pavement to overcome the damage. The method used is the 2017 Pavement Design Manual. Average daily traffic data, annual average daily traffic data, and CBR value data for soil testing using the DCP tool. Calculations using the 2017 Pavement Design Manual methodology, on a 275 mm thick concrete slab, 100 mm thick concrete layer, and 150 mm Class A aggregate drainage layer. The connection is divided into two parts, namely the longitudinal connection by binding using threads 16 - 750, and the cross connection with dowels using ordinary reinforcement D 36 - 300, the budget plan is Rp. 5,917,030,000.00.